Optical monitoring of retinal respiration in real time: 670 nm light increases the redox state of mitochondria. (November 2016) - Kaynezhad, Pardis; Tachtsidis, Ilias; Jeffery, Glen
Abstract: Mitochondria play a key role in ageing and disease. Their membrane potentials and ATP production decline with age and this is associated with progressive inflammation, cell loss and death. Here we use broadband Near-Infrared Spectroscopy (NIRS) to non-invasively measure in-vivo changes in aged retinal mitochondrial respiration following exposure to 670 nm, which improves mitochondrial performance and reduces inflammation. Low power NIR light was shone into the eye via a fibre optic and the reflection monitored to measure signature changes in the oxidation of cytochrome c oxidase (COX) in complex IV of the electron transport chain. Changes in retinal haemodynamics and oxygenation were also recorded simultaneously with COX by measuring changes in oxygenated and deoxygenated haemoglobin (Δ[HbO2 ] and Δ[HHb]). Retinae of aged rats exposed to 670 nm for 5 mins showed consistent progressive increases in oxidation of COX 5 mins post exposure. This remained significantly greater than baseline for up to 2 h. This was not seen when retinae were exposed to 420 nm light of the same power or when no light was applied. 670 nm exposure significantly increased total haemoglobin concentration (Δ[HbT] = Δ[HbO2 ] +Δ[HHb]) but not haemoglobin difference (Δ[HbDiff] = Δ[HbO2 ] -Δ[HHb]). There were no changes in blood metrics in association with 420 nm light or when no light exposure was given. Hence, brief 670 nm exposure that is associated with reduced inflammation has a significant positive impact on the redox state of COX in aged retinae. The relative redox state of retinal COX may provide a valuable biomarker in ageing and macular degeneration where declining mitochondrial function is implicated. Highlights: We measure real time retinal reflections in vivo in rats. We isolate signals from oxy/deoxy haemoglobin and those from relative COX redox. 670 nm increases COX redox and total haemoglobin improving mitochondrial function. These measurements monitor retinal respiration and may be a biomarker for disease.